Revisiting of Pd Nanoparticles in Cancer Treatment: All-Round Excellence of Porous Pd Nanoplates in Gene-Thermo Combinational Therapy - Kang, Seounghun; Shin, Woojun; Kang, Kyunglee; Choi, Myung-Ho; Kim, Young-Jin; Kim, Young-Kwan; Min, Dal-Hee; Jang, Hongje (American Chemical Society, 2018)
Gold nanomaterials are commonly used in biomedical applications owing to their excellent biocompatibility and unique physicochemical and optical properties, whereas Pd nanomaterials are mainly used as catalysts. Here, we re-examined the possible applications of Pd nanomaterials. Reducing agent-assisted excessive galvanic replacement-mediated porous Au nanoplates, porous Pt nanoplates, and porous Pd nanoplate synthesis enabled us to compare the properties and efficiency of nanoplates composed of three metal elements (Au, Pt, and Pd). According to our analytical results, porous Pd nanoplates exhibited exceptional all-round excellence in photothermal conversion, therapeutic gene loading/releasing, cytotoxicity, and in vitro combination cancer treatment. We believe that this discovery broadens the potential applications of metal nanomaterials, with an emphasis on more efficient biomedical applications in limited conventional fields.
Keywords: GALVANIC REPLACEMENT; GOLD NANOPARTICLES; DRUG-DELIVERY; PLATINUM NANOPARTICLES; POLYMERIC NANOPARTICLES; HOLLOW NANOSTRUCTURES; FACILE SYNTHESIS; SIZE; CONJUGATION; AGGREGATION